Penggunaan Media Audio Visual Pada Pembelajaran Fiqih Untuk Meningkatkan Prestasi Belajar Siswa Kelas VIII di MTs Nurus Salam - Yusril Nasution; Hasnil Aida Nasution; Dahrul Dahrul (Journal of Innovative and Creativity, 2025)
This study aims to describe the implementation of the role-playing method in the teaching of Islamic Cultural History (Sejarah Kebudayaan Islam or SKI), specifically on the topic of the Khulafaur Rasyidin, for tenth-grade students at MAS Al Washliyah Tanjung Beringin. Using a qualitative descriptive approach, data were collected through classroom observation, interviews with teachers and students, and documentation. The findings indicate that the role-playing method enhances student engagement, understanding, and appreciation of the values exemplified by the Khulafaur Rasyidin. Students became more active and enthusiastic during the learning process, as they were given the opportunity to portray historical figures such as Abu Bakr, Umar, Uthman, and Ali. This method not only helped improve their retention of historical facts but also internalized Islamic values such as leadership, justice, integrity, and courage. The study concludes that role-playing is an effective and innovative method for teaching SKI, especially in conveying moral and spiritual lessons through historical narratives.